Acute Respiratory Distress Syndrome Associated with Tumour Lysis Syndrome in Leukemia - Chaim M Bell; Thomas E Stewart (Canadian Respiratory Journal)
Acute tumour lysis syndrome (ATLS) developed in two patients with acute myelogenous leukemia soon after they were treated with cytosine arabinoside. The patients also developed respiratory distress requiring intubation. Autopsy and clinical findings demonstrated the presence of acute respiratory distress syndrome (ARDS). An association appears to be present between ARDS and ATLS in this group of patients.